PENINGKATAN KETRAMPILAN MENYIMAK PELAJARAN BAHASA INDONESIA MELALUI PERMAINAN BISIK BERANTAI - Resti Alviolita; Desy Arisandy (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2020)
This study aims to look at the influence of chain whispering games on the skills of listening to Indonesian in third grade students at SD N 101 Palembang. This study uses the experimental design of One Group Pretest-Posttest. The research subjects were 10 third grade students of SD N 101 Palembang, which were grouped into one experimental group. The sampling technique used is purposive sampling. To measure listening skills used a learning achievement test measuring instrument in the form of multiple choice questions.At the pretest, subjects were given a pretrial study only, and then were given a four-day whiskey game treatment. After treatment, participants were given a posttest using achievement tests. The data in this study were analyzed using paired sample t-test techniques, the results of the analysis obtained a very significant influence on the whisper chain game on listening skills with a p value of 0,000 (p <0.05) and a value of t = 6.042. Based on these results it can be concluded that the chain whispering game affects the listening skills of Indonesian language lessons in third grade children at SD N 101 Palembang